Histopathology of diffusion imaging abnormalities in cerebral amyloid angiopathy. (26th February 2019) - van Veluw, Susanne J.; Reijmer, Yael D.; van der Kouwe, Andre J.; Charidimou, Andreas; Riley, Grace A.; Leemans, Alexander; Bacskai, Brian J.; Frosch, Matthew P.; Viswanathan, Anand; Greenberg, Steven M.
Abstract : Objective: We sought to determine the underlying mechanism for altered white matter diffusion tensor imaging (DTI) measures at the histopathologic level in patients with cerebral amyloid angiopathy (CAA). Methods: Formalin-fixed intact hemispheres from 9 CAA cases and 2 elderly controls were scanned at 3-tesla MRI, including a diffusion-weighted sequence. DTI measures (i.e., fractional anisotropy [FA] and mean diffusivity [MD]) and histopathology measures were obtained from 2 tracts: the anterior thalamic radiation and inferior longitudinal fasciculus. Results: FA was reduced in both tracts and MD was increased in cases with CAA compared to controls. Regional FA was significantly correlated with tissue rarefaction, myelin density, axonal density, and white matter microinfarcts. MD correlated significantly with tissue rarefaction, myelin density, and white matter microinfarcts, but not axonal density. FA and MD did not correlate with oligodendrocytes, astrocytes, or gliosis. Multivariate analysis revealed that tissue rarefaction (β = −0.32 ± 0.12, p = 0.009) and axonal density (β = 0.25 ± 0.12, p = 0.04) were both independently associated with FA, whereas myelin density was independently associated with MD (β = −0.32 ± 0.12, p = 0.013). Finally, we found an association between increased MD in the frontal white matter and CAA severity in the frontal cortex ( p = 0.035). Conclusions: These results suggest that overall tissue loss, and in particular axonal and myelin loss, are major components underlying CAA-related alterations in DTI properties observed in living patients. The findings allow for a more mechanistic interpretation of DTI parameters in small vessel disease and for mechanism-based selection of candidate treatments to prevent vascular cognitive impairment.